Расчетное и экспериментальное исследование устойчивой работы смешивающих ПНД для ТЭС и АЭС - Синцова, Т. Г.; Трифонов, Н. Н.; Ермолов, В. Ф.; Сухоруков, Ю. Г. (НТУ "ХПИ", 2014)
ОАО «НПО ЦКТИ» разработало методику расчета системы смешивающих подогревателей низкого давления, включенных по гравитационной схеме, совместно с конденсатными электронасосами второй ступени. В статье представлены описание и результаты статических и динамических испытаний смешивающих подогревателей низкого давления энергоблока №4 Калининской АЭС. Сопоставление результатов расчета с опытными данными, полученными при испытаниях, показало их достаточно хорошее совпадение.

One of the methods used for an increase in the operation efficiency of the turbine plant is considered to be the use of low pressure heaters of a mixing type for the regeneration system. A broad application was found for the gravitation diagram in which mixing heaters are arranged at different heights to provide the possibility of the use of the gravity water overflow from the heater with a lower steam pressure to the heater with a higher steam pressure. However this diagram requires taking additional measures to provide reliable operation of the regeneration system. PJSC "NPO CKTI" developed a technique for the design of the system of mixing heaters of low pressure that are connected according to the gravitational scheme together with condensate electric pumps of the second stage for the purpose of the study of their operation in the regeneration system. The results of statistical and dynamic tests of the mixing heaters of low pressure for the power unit No 4 at Kalinin NPS have been given. The comparison of computational data and experimental data that were obtained during the tests showed their satisfactory matching.
Design and experimental studies of the stable operation of mixing low pressure heaters for thermal power stations and nuclear power stations
Keywords: смешивающий подогреватель; сброс нагрузки; испытания; безопасность; mixing heater; load dropping; tests; safety